Anthelmintic activity of Artemisia vestita Wall ex DC. and Artemisia maritima L. against Haemonchus contortus from sheep - Irum, Shamaila; Ahmed, Haroon; Mukhtar, Muhammad; Mushtaq, Muhammad; Mirza, Bushra; Donskow-Lysoniewska, Katarzyna; Simsek, Sami (Elsevier Science Bv, 2015)
Current study was designed to evaluate in vivo and in vitro anthelmintic activity of Artemisia vestita Wall ex DC. and Artemisia maritima L. against Haemonchus contortus in comparison with ivermectin to investigate the effect of plant extracts on survival of infective L-3 and adults under in vitro condition. Plant extracts were given to H. contortus infected sheep orally and it was infected with L-3 stage of H. contortus at dose of 5000 larvae/sheep. Total of 25-30 larvae were incubated with plant extracts in PBS alone and ivermectin at different concentration used as positive control. It was recorded that there is a significant decrease in fecal egg count (FEC) after post-treatment period for both plants. The highest fecal egg count reduction for A. vestita was 87.2% at 100 mg/kg while for A. maritima it was 84.5% on day 28 post-treatment. Investigated extracts indicated significant activity against larvae and adult worms. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Haemonchus contortus; Anthelmintic; Plants; Artemisia vestita; Artemisia maritima